Phytochemical Evaluation and Metabolic Profiling of Methanolic Extracts from the Stem and Leaf of Suregada multiflora (A. Juss.) Baill.: An Ethnobotanically Important Medicinal Plant - S S, Usha (Asian Journal of Biological and Life Sciences)
Aim: In Indian traditional knowledge; many plants are documented for their therapeutic usage. Secondary metabolites are responsible for this pharmacological potentiality. Suregada multiflora, known as false lime, is used traditionally for the treatment of many diseases. Therefore, the present study was undertaken to evaluate the phytochemical profile of stem and leaf methanolic extracts from S. multiflora to substantiate their therapeutic efficacy. Materials and Methods: Physicochemical evaluation was undertaken to check its usage in crude drug formulations; it was followed by the phytochemical analysis of the stem and leaf using non-polar to polar solvents. Methanolic extracts of stem and leaf were subjected to HPTLC analysis, and to identify the compounds, LCMS analysis was carried out. Results: Preliminary phytochemical analysis showed that the methanolic extract of stem and leaf comprises a remarkable number of phytoconstituents. It was further substantiated with HPTLC analysis in terms of the total number of peaks, peak heights, peak area, percent area and Rf values. Following this, LC-MS analysis was conducted, and positive ionization of the leaf revealed 47 components, while the negative mode showed 60 identified molecules. Similarly, the positive ionization of the stem showed 41 components, and the negative ionization of the stem showed 58 identified components. Conclusion: Methanolic extract of S. multiflora stem and leaf contains a pool of phytochemicals which might be accountable for its therapeutic value and justifies its traditional usage.
Keywords: Physico-chemical standardization; Qualitative Phytochemistry; Spectrophotometry.; Suregada multiflora